Competitive Release in Diets of Ocelot (Leopardus pardalis) and Puma (Puma concolor) After Jaguar (Panthera onca) Decline - Moreno, R. S.; R. W. Kays; Samudio Jr., R. (Journal of Mammalogy, 2006)
We used fecal analyses to document the diet of ocelots (Leopardus pardalis) and puma (Puma concolor) at 2 sites in central Panama. We detected puma on Barro Colorado Island (BCI) nearly every month during the study but never found evidence of jaguars (Panthera onca) at either site. Both ocelots and puma fed predominantly on mammalian prey, but consumed a diversity of species. Collared peccaries (Pecari tajacu) and Central American red brocket (Mazama temama) were the most important food items for puma, whereas Central American agoutis (Dasyprocta punctata) and sloths (Choloepus hoffmanni and Bradypus variegatus) were the most important for ocelots. Considerable overlap in diet was found between populations and species, but the diet of puma on BCI was significantly different from the 2 ocelot populations in containing more large prey, suggesting that dietary differences between these predator species are chiefly related to their relative body size. Comparing across larger scales, both populations of ocelots in our study ate larger prey than elsewhere in their range, suggesting that their fundamental niche includes more medium-sized prey than their realized niche in other sites. Puma on BCI ate proportionally more peccaries and deer than in most other populations. These unusual diets in the wake of a recent decline or local extinction of jaguars are consistent with a prey shift in response to competitive release.
Keywords: Barro; Carnivora; Colorado Island; competitive release; Diet; felid; predation